Digital Extensive Reading in Indonesia: A Critical Review - Karunia Eka Nafilatul Janah; Pratiwi Retnaningdyah; Ali Mustofa (Journal of English Language Teaching and Linguistics, 2022)
Several previous studies have revealed that extensive reading is essential for supporting the success of EFL students’ language learning. Due to the advancement of technology that has entered the language classroom, the implementation of extensive reading programs in Indonesia has shifted to digital extensive reading, where both EFL students and teachers utilize digital materials or tools through various applications or online platforms. Hence, this paper aims to critically review digital extensive reading in Indonesia to provide an overview or information regarding the implementation of digital extensive reading in Indonesia. Following George’s (2008) Literature Reviews model, twelve articles related to digital extensive reading in Indonesia that were published from 2019 to 2022 in reputable national journals were critically reviewed. It was revealed that the digital extensive reading in Indonesia was implemented variously through several digital or online platforms for extensive reading, such as Let’s Read! application, Blogging, Mobile-Assisted, Xreading, Wattpad, Webtoon, and other various online platforms, such as WhatsApp, Zoom, and Google Classroom. Last but not least, it can be concluded that the implementation of digital extensive reading through those various digital or online platforms has been proven to be useful in supporting the success of EFL students’ digital extensive reading activities as well as the success of EFL students’ language learning.